Clinical interpretation of whole-genome and whole-transcriptome sequencing for precision oncology. (September 2022) - Jobanputra, Vaidehi; Wrzeszczynski, Kazimierz O.; Buttner, Reinhard; Caldas, Carlos; Cuppen, Edwin; Grimmond, Sean; Haferlach, Torsten; Mullighan, Charles; Schuh, Anna; Elemento, Olivier
Abstract: Whole-genome sequencing either alone or in combination with whole-transcriptome sequencing has started to be used to analyze clinical tumor samples to improve diagnosis, provide risk stratification, and select patient-specific therapies. Compared with current genomic testing strategies, largely focused on small number of genes tested individually or targeted panels, whole-genome and transcriptome sequencing (WGTS) provides novel opportunities to identify and report a potentially much larger number of actionable alterations with diagnostic, prognostic, and/or predictive impact. Such alterations include point mutations, indels, copy- number aberrations and structural variants, but also germline variants, fusion genes, noncoding alterations and mutational signatures. Nevertheless, these comprehensive tests are accompanied by many challenges ranging from the extent and diversity of sequence alterations detected by these methods to the complexity and limited existing standardization in interpreting them. We describe the challenges of WGTS interpretation and the opportunities with comprehensive genomic testing.